STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK TUNA RUNGU DAN TUNA GRAHITA DI SEKOLAH LUAR BIASA NEGERI MUSI RAWAS - Ika Lathifah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2017)
The purpose of the study describes  the learning  strategy of Islamic education in the deaf children  and  the mentally disabled  children  as well as inhibiting factors and  factors supporting the learning  of Islamic religious education. This research is a qualitative  research  that  is a field research  that  is descriptive.  Data  collection  techniques: observation, interviews,  and documentation. Data analysis techniques: data  reduction, data  presentation and  conclusions.  The result of this research  is the learning strategy of Islamic education in deaf children is selected according  to the needs of each student  and the strategy used is the expository,  inquiry, contextual  teaching  learning and  individualization strategies and  learning strategy of Islamic education in the mentally disabled  children with more  attention to the needs  and  capacity  Ability of each  student,  strategy used,  among others,  active teacher  learning strategy and individualization. The inhibiting factors found are not maximally the role of parents to teach the understanding of religion at home,  the absence of special teachers  Islamic education, students who have limitations that require a long process while the supporting factors are a comfortable learning environment, enthusiastic  students,  teachers who are creative in learning Islamic education, the principal who supports  teaching  and learning activities